A green IT/IS assessment model for attaining sustainability in Malaysia collaborative enterprise - Junior, Bokolo Anthony (2018)
Sustainability has progressively become significant in Collaborative Enterprise (CE), thus Information Technology (IT) practitioners are beginning to practice Green IT/IS initiatives by also utilizing manual self-assessment methods based on checklists questionnaire and ISO 14001 standards to attain sustainability. Similarly, the literature on Green IT/Information Systems (IS) practices for attaining sustainability in CE is still in its infancy and there is little research on how to assess Green IT/IS practice. But, existing Green Information Technology (IT) assessment models focus on energy efficiency in reducing the negative impacts of IT. Moreover, CE assess Green IT/IS practices by only considering recycling operation and ignoring other Green IT/IS practices. This is mainly due to the prospect that recycling is synonymous with Green IT/IS practices. Consequently, there is need to provide the Green IT/IS practice to be implemented by IT practitioners in CE based on an easy-to-use but comprehensive model to assess CE current Green IT/IS practice in attaining economic, social and environmental sustainability. Similarly, existing assessment models only raises awareness on the potential of Green IT/IS and offer little practical guidelines to assess Green IT/IS for attaining sustainability. Besides, there are independent variables that influences Green IT/IS practice in CE, hence there is a need for an assessment model that can be utilized by CE to ensure that IT practitioners considers these variables when implementing Green IT/IS practice in attaining sustainability in CE operations. Therefore, this study proposes a Green IT/IS assessment model based on Belief-Action-Outcome (BAO) framework to aid IT practitioners in assessing their current Green IT/IS practice towards attaining sustainability. BAO framework is suitable for this study, because the framework propose links between the influence of Green IT/IS assess on IT practitioner’s beliefs about the environment and the influence of their beliefs on Green IT/IS practice actions and subsequent outcomes. Accordingly, in order to develop the Green IT/IS assessment model, this study identifies the Green IT/IS practices to be implemented in CE and independent variables that influences Green IT/IS practice in CE for attaining sustainability. In addition, the model constitutes social-demographic determinants (moderating variables) and enterprise characteristics (control variables). This study opted for pragmatic paradigm (qualitative and quantitative approach) using purposive sampling technique to collect data from case study (interview and Green IT/IS documents), online survey and focus-group questionnaire. The case study was carried out in two higher eductaion institutions and two organizations which comprises of fifteen informants who provided data to verify the Green IT/IS practices and independent variables derived from the literature. Then, data was collected using online survey from one hundred and thirty-three respondents in CE based in Malaysia to validate the developed Green IT/IS assessment model. Likewise, a Green IT/IS Assessment Tool (GAT) was implemented to further validate the applicability of the Green IT/IS assessment model by carrying out focus-group questionnaire by collecting data from thirty-five IT practitioners. Results from this research reveals that the independent variables influences Green IT/IS practices, and the identified Green IT/IS practices are significant and should be implemented by IT practitioners in CE for attaining economic, social and environmental sustainability. The Green IT/IS assessment model can help CE towards reorienting their current corporate performance for a sustainable future and also assist IT practitioners to explicitly acknowledge enterprise areas to be recognized, resolved and further improved.